2022
DOI: 10.1111/jerd.12948
|View full text |Cite
|
Sign up to set email alerts
|

Five‐year clinical performance of two fluoride‐releasing giomer resin materials in occlusal restorations

Abstract: Objective To evaluate and compare the clinical performance of two nano‐hybrid giomer restorative composite materials after 5 years. Materials and Methods Forty‐four pairs of restorations (total n = 88) of a flowable giomer (Beautifil Flow Plus F00; Shofu Inc., Kyoto, Japan) and a conventional nano‐hybrid giomer restorative material (Beautifil II; Shofu Inc.) were placed in Class I cavities after the application of a dentin adhesive (FL‐Bond II; Shofu Inc.) and a flowable liner (Beautifil Flow Plus F03; Shofu I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
3
0
1
Order By: Relevance
“…They described that such surface alteration was caused by dissolution of S-PRG filler. Although several clinical studies revealed their excellent performance [35,36], long-term surface durability of S-PRG filler-containing resin composites remains to be investigated in detail.…”
Section: Restorative Treatmentmentioning
confidence: 99%
“…They described that such surface alteration was caused by dissolution of S-PRG filler. Although several clinical studies revealed their excellent performance [35,36], long-term surface durability of S-PRG filler-containing resin composites remains to be investigated in detail.…”
Section: Restorative Treatmentmentioning
confidence: 99%
“…Outros estudos de EDX, contração de polimerização, espectrofotometria de massa e análise de íons específicos apresentam resultados promissores quanto ao uso de partículas bioativas mesmo levando em consideração o uso de diferentes materiais 42,43 .…”
Section: Introductionunclassified

Características De Compômeros Contendo Partículas Bioativas: Uma Revisão Integrativa

Samara de Freitas Guimarães,
Geovana Manoela Amaral,
Lucas Vinícyus Lima Maia Miranda
et al. 2024
cpaqv
“…Giomers differ from glass ionomers and resin modified glass ionomers in having surface salinized prereacted glass (S-PRG) fillers incorporated within the resin matrix 15,16 . The addition of S-PRG fillers improves the physical and mechanical properties and increases fluoride releasing and recharging over time 17,18 .…”
Section: Introductionmentioning
confidence: 99%